2020
DOI: 10.1002/col.22507
|View full text |Cite
|
Sign up to set email alerts
|

The impact of color preference on adolescent children's choice of furniture

Abstract: It is widely believed that children will choose furniture that has the same color as their preferred color. Furthermore, for different categories of furniture, the color they preferred for furniture is consistent. A study of 508 adolescent Chinese children between the ages of 12 and 16 has been carried out to explore whether color preference influences their choice of furniture when they are provided with various color options (16 chromatic and five achromatic colors). This work tested six items of furniture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 62 publications
5
50
1
1
Order By: Relevance
“…Finding an efficient way to understand individual colour preference is important to researchers 52 and designers 53 . From the previous studies, a colour preference research strategy includes experimental environment and research method with various different circumstance, such as a various of number of colour‐samples or number of participants .…”
Section: Framework For Colour Preferencementioning
confidence: 99%
“…Finding an efficient way to understand individual colour preference is important to researchers 52 and designers 53 . From the previous studies, a colour preference research strategy includes experimental environment and research method with various different circumstance, such as a various of number of colour‐samples or number of participants .…”
Section: Framework For Colour Preferencementioning
confidence: 99%
“…Demir researched the effect of the interface background color choice on the emotion of university students, which was considered to be a good reference on color perception and color design for software interface designers 11 . In the work of Jiang et al, findings showed that adolescent children's color preferences affect their furniture choice, but the extent varies with the categories of furniture 12 . Yu et al studied color composition in travel‐related photos on Instagram.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, individual colour preferences do affect participants' purchase decisions. 19,23,24 To explore the connection between colour-association and product-colour-association, the "template approach" analysis method 25 was used (NVivo software) to code and organize qualitative data from interviews. The three sequential steps for the template approach were as follows: (a) creating a coding scheme for each colour name; (b) coding the data to each colour; (c) gathering similar data in one place.…”
Section: Resultsmentioning
confidence: 99%
“…Each filled diamond symbol represents one product (selected products are identified using an icon) or colour schemes. From the authors' previous research, consumers' product-colour decisions are often connected with consumers' individual colour preference, 19,23,24 expected function or performance depending on the type of products. Consumers' personal colour preference may be important, but only in the absence of primary factors that will otherwise drive a product-colour purchase behavior.…”
Section: Discussionmentioning
confidence: 99%